PENGARUH TEAM WORK DAN KINERJA KARYAWAN TERHADAP BUDAYA ORGANISASI DI PABRIK PUPUK - Muhammad Ilham Nurdini; Moch. Nuruddin (LPPM Politeknik LP3I Medan, 2021)
Human resources play a very significant role in the running of an organization or company to manage the running of the company's system optimally so that it can support the achievement of the goals of the organization or company. But the problem that is often faced by companies today is how to create human resources that can produce optimal performance and in accordance with what the company expects. This research was conducted at a fertilizer plant in the city of East Java with the main activity of supplying national fertilizer needs. This company includes advanced companies so the demand for fertilizer production is also increasing. With these conditions, the role of employees becomes an important factor for the company in realizing the vision and mission of the company. The company always strives to improve the internal quality of the company in order to compete with competing companies. One of the efforts made is an assessment of employee performance and team work. The purpose of research is to assess the influence and interrelationships between dependent variables (organizational culture) and independent (employee performance and team work). This research population is employees in fertilizer companies who understand the problems and people who are experts in their fields to ensure the data generated is relevant and in accordance with the purpose of the research. The sample used to fill out the variable questionnaire amounted to 52 employees.The methods used are statistical analysis of multiple linear regression, test F and coefficient of determination. The results of research and analysis conducted by researchers showed that independent variables namely team work (X1) and employee performance (X2) simultaneously or together had a positive influence and significance on dependent variables namely organizational culture (Y). Or in other words, if the dependent variable increases, it will be accompanied by an increase in independent variables.